Applicability of polyethylene glycol precipitation followed by acid guanidinium thiocyanate-phenol-chloroform extraction for the detection of SARS-CoV-2 RNA from municipal wastewater - Torii, Shotaro (Sci Total Environ, 2021)
The primary concentration and molecular process are critical to implement wastewater-based epidemiology for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, the previously developed methods were optimized for nonenveloped viruses. Few studies evaluated if the methods are applicable to the efficient recovery of enveloped viruses from various types of raw sewage. This study aims (1) to compare the whole process recovery of Pseudomonas phage φ6, a surrogate for enveloped viruses, among combinations of primary concentration [ultrafiltration (UF), electronegative membrane vortex (EMV), and polyethylene glycol precipitation (PEG)] and RNA extraction methods (spin column-based method using QIAamp Viral RNA Mini Kit and acid guanidinium thiocyanate–phenol–chloroform extraction using TRIzol reagent) for three types of raw sewage and (2) to test the applicability of the method providing the highest φ6 recovery to the detection of SARS-CoV-2 RNA. Among the tested combinations, PEG+TRIzol provided the highest φ6 recovery ratio of 29.8% to 49.8% (geometric mean). UF + QIAamp Viral RNA Mini Kit provided the second highest φ6 recovery of 6.4% to 35.8%. The comparable φ6 recovery was observed for UF + TRIzol (13.8–30.0%). PEG + QIAamp Viral RNA Mini Kit provided only 1.4% to 3.0% of φ6 recovery, while coliphage MS2, a surrogate for nonenveloped viruses, was recovered comparably with PEG + TRIzol. This indicated that the nonenveloped surrogate (MS2) did not necessarily validate the efficient recovery for enveloped viruses. EMV + QIAamp Viral RNA Mini Kit provided significantly different φ6 recovery (1.6–21%) among the types of raw sewage. Then, the applicability of modified PEG + TRIzol was examined for the raw sewage collected in Tokyo, Japan. Of the 12 grab samples, 4 were positive for SARS-CoV-2 CDC N1 and N3 assay. Consequently, PEG + TRIzol provided the highest φ6 recovery and allowed for the detection of SARS-CoV-2 RNA from raw sewage.